Clinical Characteristics and Pattern of Imaging Change of Pediatric COVID-19 (Medicine Today, 2023)
Introduction: COVID-19 infection in children is relatively milder and vary from that in adults. Higher fatality rate of children in Bangladesh from COVID-19 infection does not matched with other country may be due to malnutrition, air pollution, poverty, poor parental education about health hygine, inadequate access to high-quality acute healthcare. Chest X-ray is initial imaging technique which is done in children with mild respiratory infections with or without dyspnea. Few studies have reported the radiological findings of COVID-19 in children.Objective: In this study, our main goal was to investigate the clinical and imaging features of pediatric COVID-19 patients in child corona unit of Dhaka Medical College Hospital, Bangladesh.Materials and Methods: This single center observational study was conducted in Child Corona Unit of Dhaka Medical College Hospital between January 2022 to September 2022. A total of 123 COVID-19 positive pediatric patients detected by RT-PCR were purposively included in the study. Patients with comorbidities were excluded from the study.Results: Among 123 children with COVID-19, 43 had no symptoms, 71 had low grade fever and 9 presented with cough, nasal congestion, diarrhea, headache, or fatigue. Normal X-ray findings present in 50(40.6%), unilateral patchy shadowing in 28 (22.8%), bilateral patchy shadowing in 22(17.9%), ground glass opacity in 11(8.9%), consolidation in 7(5.8%) and Interstitial abnormalities in 5(4.0%).Conclusion: This study throw light on the cases of COVID-19 in the pediatric population. Children usually have mild or moderate clinical and imaging presentations. Understanding of the clinical and imaging findings helps in reducing misdiagnosis rate for those with concealed and atypical symptoms.Medicine Today 2023 Vol.35(1): 7-11